2007
DOI: 10.1002/dvdy.21382
|View full text |Cite
|
Sign up to set email alerts
|

Temporal–spatial ablation of neural crest in the mouse results in cardiovascular defects

Abstract: Neural crest cells are thought to play a critical role in human conotruncal morphogenesis and dysmorphogenesis. Much of our understanding of the contribution of neural crest to cardiovascular patterning comes from ablation and transplantation experiments in avian species. Although fate mapping experiments in mice suggests a conservation of function, the functional requirement for neural crest in cardiovascular development in mammals has not been formally tested. We used a novel two component genetic system for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 46 publications
(52 reference statements)
4
37
2
Order By: Relevance
“…The left 6th PAA persists during fetal development and gives rise to the ductus arteriosus (Hutson and Kirby, 2007). By contrast, in animal models with cardiac NC deficiency, PAA regression occurs at random (Leatherbury et al, 1990;Nishibatake et al, 1987;Olaopa et al, 2011;Porras and Brown, 2008). This leads to variable aberrations in the final configuration of the AAAs, similar to the phenotypes observed in our mutants (Table S2, Fig.…”
Section: Ablation Of Fn1 In the Nc Results In Cardiovascular Abnormalsupporting
confidence: 80%
“…The left 6th PAA persists during fetal development and gives rise to the ductus arteriosus (Hutson and Kirby, 2007). By contrast, in animal models with cardiac NC deficiency, PAA regression occurs at random (Leatherbury et al, 1990;Nishibatake et al, 1987;Olaopa et al, 2011;Porras and Brown, 2008). This leads to variable aberrations in the final configuration of the AAAs, similar to the phenotypes observed in our mutants (Table S2, Fig.…”
Section: Ablation Of Fn1 In the Nc Results In Cardiovascular Abnormalsupporting
confidence: 80%
“…21,34,41). To assess cardiac function in the P0 mutants, we used noninvasive fetal ultrasound biomicroscopy-Doppler imaging.…”
Section: Ubm-doppler Imaging Analysis Reveals Abnormal Blood Flow In mentioning
confidence: 99%
“…Fate mapping analyses show that cNCC contribute to the aorticopulmonary septum (OFT septum), atrioventricular valves, semilunar valves, and conduction system in the mouse heart (2,18,32,38,40,48,53). Ablation experiments have demonstrated that cNCC are indispensable for OFT septation (14,41,54). Although cNCC are found in the semilunar valves of the pulmonary artery and the aorta, the precise function of cNCC in semilunar valve development is unknown.…”
mentioning
confidence: 99%
“…WNT signaling can operate through a JNK-dependent mechanism, which involves MEKK4 (Luo et al, 2003). Because the neural crest is an important contributor to the outflow tract (Jiang et al, 2000;Porras and Brown, 2008), it could be suggested that a proportion of MEKK4-deficient mice will likely have outflow tract malformations. In this regard, MEKK4 was recently shown to regulate developmental EMT in cardiac cushion tissue or the prevalvular regions of the embryonic heart.…”
Section: Mekk4 (Omim#*602425)mentioning
confidence: 99%